Structured Decision Support for Indonesia’s Islamic P2P Platform Prioritization Using VIKOR (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study employs the VIKOR method to conduct a comprehensive assessment of Sharia-compliant financial technology entities within Indonesia’s peer-to-peer (P2P) lending ecosystem. Through the integration of multiple evaluation dimensions weighted using the Rank Sum Weighting approach, this method enables a balanced appraisal that reflects both quantitative performance and qualitative perceptions derived from structured user evaluations. VIKOR facilitates a compromise-oriented ranking process by measuring the relative closeness of each alternative to an ideal solution, effectively addressing trade-offs among conflicting criteria. The findings highlight the method’s capability to produce a systematic, transparent, and Sharia-aligned decision framework. Beyond its empirical contribution, the study demonstrates the practical applicability of multi-criteria decision-making techniques for ethical investment assessment and strengthens the anal